Macroeconomic, regulatory and market determinants of airline capacity setting. - Humberto Filipe de Andrade Januário Bettini (2007)
This dissertation aims at identifying the determinants of capacity setting in airline markets. Among these determinants, macroeconomic, regulatory and competition factors are highlighted. We take advantage of the particularity of this sector, in which firms have to commit with capacity - defined as seats available - in each market once entry decisions are made and therefore consider the variability found in a panel of routes for the Brazilian domestic scheduled airline industry. I then propose an econometric model of airline capacity formation. The main results are: 1. macroeconomic aggregates that shift demand and costs, such as GDP and exchange rate, have significant impact over the decision process of capacity setting; 2. changes imposed by some measures of re-regulation of the industry in 2003 significantly impacted capacity; and 3. a code-share agreement among the two biggest airlines in 2003 had a negative impact in airline seats supply, which is consistent with the effects of higher dominance in the market, thus justifying an increased surveillance by antitrust authorities.